The impact of compound exercises (physical) supported by information technology (GPS Ubiko and Polar H9) on developing endurance in football players - Jawad, Haitham (Journal of Physical Education, 2025)
Among the most often played team sports, football is played by players of various ages and skill levels. This sport's physical growth is mostly dependent on methodical training aided by contemporary technology, which has greatly improved athletic performance. High endurance capacity is necessary for exceptional football performance in order to maintain constant physical effort during practices and games, especially considering the competitive nature of the sport. This study aims to enhance speed endurance capacity among players of the Al-Talaba youth team (aged 19) in Baghdad by applying advanced technological tools such as the GPS Ubiko tracking device and the Heart Rate monitoring device (Polar H9). The implication of the research lies in introducing compound exercises based on modern technology, contributing to improved players’ physical performance and the development of training strategies founded on accurate data. The research highlights the necessity of developing speed endurance among players, which requires the use of modern technologies for performance analysis and the implementation of compound exercises (physical) to enhance their ability to sustain physical effort during matches. The results revealed that exercises utilizing devices such as GPS and Polar significantly improve speed endurance, highlighting the importance of mixing these technologies into sports exercise programs to achieve optimal benefits.